2019
DOI: 10.3390/pharmaceutics11020077
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanomaterials: Versatile Nanocarriers for Cancer Theranostics and Drug and Gene Delivery

Abstract: Mesoporous silica nanomaterials (MSNs) have made remarkable achievements and are being thought of by researchers as materials that can be used to effect great change in cancer therapies, gene delivery, and drug delivery because of their optically transparent properties, flexible size, functional surface, low toxicity profile, and very good drug loading competence. Mesoporous silica nanoparticles (MSNPs) show a very high loading capacity for therapeutic agents. It is well known that cancer is one of the most se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 191 publications
(223 reference statements)
0
39
0
Order By: Relevance
“…SD rBMSCs were seeded in a 96-well plate with a concentration of 5 × 10 3 cells/well and incubated overnight prior to starting the treatments. The cells were washed with PBS and transferred to a low serum medium (5% FBS) without penicillin or streptomycin, prior to treating them with varying concentrations (5,10,20,25,50, and 100 μg/mL) of MSN@PEI-KALA, MSN_miR-26a@PEI-KALA and MSN_miR-NC@PEI-KALA. The CCK-8 assay was used to assess the cell viability at 12 h and 24 h post transfection.…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…SD rBMSCs were seeded in a 96-well plate with a concentration of 5 × 10 3 cells/well and incubated overnight prior to starting the treatments. The cells were washed with PBS and transferred to a low serum medium (5% FBS) without penicillin or streptomycin, prior to treating them with varying concentrations (5,10,20,25,50, and 100 μg/mL) of MSN@PEI-KALA, MSN_miR-26a@PEI-KALA and MSN_miR-NC@PEI-KALA. The CCK-8 assay was used to assess the cell viability at 12 h and 24 h post transfection.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Mesoporous silica nanoparticles (MSNs), which have high porosity and specific surface area, tunable size, ideal biodegradability, and biosafety, were well accepted as a perfect drug delivery vehicle or system, therefore a promising vehicle for gene transfection. [24][25][26] Following the development of MSM-41-type MSN nano-vehicles for drug delivery in 2001, various types of MSNs have been designed on the basis of customized payloads that aim to deliver, e.g., bioactive molecules, plasmids, siRNA and DNA, and so on. [27][28][29][30] Advances have been made particularly in the application of MSNs as BTE scaffolds or at least a part of scaffolds in the recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the MSNs have stood out in different biomedical fields such as molecular imaging (fluorescence and magnetic resonance imaging) and drug delivery [39][40][41][42][43][44][45]. Especially in this last research area, MSN have shown a lots of benefits [46] such as a variable and controllable particle and pore size, a large surface area that can be selectively functionalized for drug delivery or high biocompatibility [47][48][49] or the possibility of combining several functionalities in a single nanosystem [50]. In this sense, one of these possible combinations is represented by the theranosis or the generation of a single nanoentity able to combine therapeutic and diagnostic features at the same time [28,[51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its excellent properties, such as its biocompatibility, high specific surface area and versatility on its surface functionalization, several challenges remain. Some of them are related to toxicity in certain tissues, clinical translation, industrial scaling, and optimization in specific drug delivery in the desired therapeutic target, in order to be incorporated as pharmaceutical products [6][7][8][9]. To overcome some of these drawbacks, bio-inspired, bio-mimetic, and smart materials, among others, have been developed [10][11][12].…”
Section: Introductionmentioning
confidence: 99%